ANALISIS PENYALURAN PEMBIAYAAN MODAL KERJA TERHADAP PENINGKATAN PENDAPATAN NASABAH BANK KALTIMTARA SYARIAH TANJUNG REDEB: ANALISIS PENYALURAN PEMBIAYAAN MODAL KERJA TERHADAP PENINGKATAN PENDAPATAN NASABAH BANK KALTIMTARA SYARIAH TANJUNG REDEB - Rita Fitriani (ECO-BUILD, 2020)
The purpose of this study was to determine whether customer income increased aftes working Capital Financing assistance at Bankaltimtara Syariah Tanjung Redeb. The analytical tool used is the standard deviation and the different t test. Based on the analysis, it can be stated that the average customer income before receiving working Capital Financing is IDR 2.372.000,- and the average income calculated after receiving working Capital Financing is IDR 5.577.000,-. The standard deviation of customer income before receiving working Capital Financing is IDR 3.224.000,-. While the standar deviation value after receiving working Capital Financing is IDR 4.970.000,-. The value of arithmetic (th) difference is 3,387. While the value of t in the table (td) is 2,022 different. Because the value of th is greater than td, (th > td), the research hypothesis is accepted, meaning that the income of customer who receive working Capital Financing at Bankaltimtara Syariah Tanjung Redeb increases.